Regulation of tumor immunity and immunotherapy by the tumor collagen extracellular matrix - Flies, Dallas B.; Langermann, Solomon; Jensen, Christina; Karsdal, Morten A.; Willumsen, Nicholas (Frontiers in Immunology, 2023)
It has been known for decades that the tumor extracellular matrix (ECM) is dysfunctional leading to loss of tissue architecture and promotion of tumor growth. The altered ECM and tumor fibrogenesis leads to tissue stiffness that act as a physical barrier to immune cell infiltration into the tumor microenvironment (TME). It is becoming increasingly clear that the ECM plays important roles in tumor immune responses. A growing body of data now indicates that ECM components also play a more active role in immune regulation when dysregulated ECM components act as ligands to interact with receptors on immune cells to inhibit immune cell subpopulations in the TME. In addition, immunotherapies such as checkpoint inhibitors that are approved to treat cancer are often hindered by ECM changes. In this review we highlight the ways by which ECM alterations affect and regulate immunity in cancer. More specifically, how collagens and major ECM components, suppress immunity in the complex TME. Finally, we will review how our increased understanding of immune and immunotherapy regulation by the ECM is leading towards novel disruptive strategies to overcome immune suppression.